2019
DOI: 10.1111/1475-6773.13197
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug monitoring programs: Assessing the association between “best practices” and opioid use in Medicare

Abstract: Objective To estimate the impact of implementing prescription drug monitoring program (PDMP) best practices on prescription opioid use. Data Sources 2007–2012 Medicare claims for noncancer pain patients, and PDMP attributes from the Prescription Drug Abuse Policy System. Study Design We derived PDMP composite scores using the number of best practices adopted by states (range: 0‐14), classifying states as either no PDMP, low strength (0 < score < median), or high strength (score ≥ median). Using generalized lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A summary of the identified intervention studies is presented in Table 15. [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] The descriptions are organized by topic (or purpose) of the interventions, by level of the intervention (screening, patient, clinician, and healthcare system), then by study. Appendix D Tables D-4 to D-6 include further details of each study.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…A summary of the identified intervention studies is presented in Table 15. [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] The descriptions are organized by topic (or purpose) of the interventions, by level of the intervention (screening, patient, clinician, and healthcare system), then by study. Appendix D Tables D-4 to D-6 include further details of each study.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…Overall, half of the studies involved patients [9,18,22–24,26,27,32,34,36–38,41–43,45,46,48,50,53,54,59,62,63,65,66,71,73,75,77–80,84–86,88,90,93,95,97,98,100,101,104,105,108–110,115–118,121,123,125,130,131,134,140,144,146,147,149,151,152,154–156,158,159,161,163,165,167] and 47% included health‐care providers [11,19,20,25,29,30,33,35,37,39,40,43,44,49,51,54–61,67–69,71,72,74,76,80–83,87,91,93,94,96,102,103,106,111–114,119,120,122,124,125,127,128,130,132,133,136–139,141,143,145,147,148,150,153,157,160,162,165]. Some studies included both patient and provider populations [36, 37, 54, 59, 80, 93, 130, 147, 166].…”
Section: Resultsmentioning
confidence: 99%
“…The extracted data from the included studies were then classified into main conceptual categories and summarised to align with the scoping review objective and research questions. The data extraction results are presented in Tables S1 and S2 [18–166], Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…[94][95][96][97][98][99] ThesepositivefindingsonstrongPDMPswere notuniform:1studyfoundnosignificantassociationbetween mandatory use requirements and the number of opioid prescriptions among patients undergoing general surgical procedures 100 and another study found that strong and weak PDMPs were associated with similar changes in opioid prescription rates, the number of cumulative doses, and prescriptionlength(indays)amongMedicarebeneficiaries. 101 Studies published after our review period investigated GoodSamaritanlaws,painclinicandmarijuanaregulations, prescribing guidelines, and educational interventions. Evidence in more recent studies refutes positive findings from the studies in our review.…”
Section: Discussionmentioning
confidence: 99%